2023
DOI: 10.1186/s12889-023-15065-4
|View full text |Cite
|
Sign up to set email alerts
|

“Before I was like a Tarzan. But now, I take a pause”: mixed methods feasibility study of the Naungan Kasih parenting program to prevent violence against children in Malaysia

Abstract: Background Despite impressive strides in health, social protection, and education, children continue to experience high rates of child maltreatment in Malaysia. This mixed-methods study assessed the feasibility of a five-session, social learning-based parenting program delivered by government staff in a community setting to reduce violence against children. Methods Parents of children from birth to 17 years were recruited from two communities near … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…J.Lachman et al (2020) found no difference between skillful parenting programs and control groups in violence against children (namely, general maltreatment, physical and emotional abuse, and neglect) and positive parenting reported by children. J. M.Lachman et al (2023) found no pre-post reductions in child-reported maltreatment outcomes (namely, general child maltreatment, physical abuse, emotional abuse, and neglect) or improvements in positive parenting behaviors.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…J.Lachman et al (2020) found no difference between skillful parenting programs and control groups in violence against children (namely, general maltreatment, physical and emotional abuse, and neglect) and positive parenting reported by children. J. M.Lachman et al (2023) found no pre-post reductions in child-reported maltreatment outcomes (namely, general child maltreatment, physical abuse, emotional abuse, and neglect) or improvements in positive parenting behaviors.…”
Section: Resultsmentioning
confidence: 79%
“…Of the 22 trials that measured parenting strategies, J. M.Lachman et al (2023), Puffer et al (2017), and Jocson et al (2023) did not find that parenting programs significantly improved positive parenting or reduced negative parenting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger RCT ( N = 296) conducted in the same context indicated an immediate improvement in observed positive parenting and positive child behaviors, and its effects persisted for one year (Ward et al, 2020). In addition, the PLH-YC and its adapted versions have been expanded to LMICs in Asia, such as Thailand, the Philippines, and Malaysia (Lachman et al, 2023; Mamauag et al, 2021; McCoy et al, 2021). McCoy et al (2021) conducted a single-group pre–post pilot study in rural Thailand using the local public health system and found that the adapted PLH-YC reduced overall maltreatment, physical and emotional abuse, and child neglect.…”
mentioning
confidence: 99%